Analyzing growth and mortality in a subtropical urban forest ecosystem (2012)
Information on urban tree growth, mortality and in-growth is currently being used to estimate urban forest structure changes and ecosystem services such as carbon sequestration. This study reports on tree diameter growth and mortality in 65 plots distributed among four land use categories, which were established in 2005/2006 in Gainesville, Florida, USA and were re-measured in 2009. Models for mortality and in-growth models were developed by grouping species into hardwoods and softwoods. Annual change in tree diameter at breast height growth was analyzed using three tree species groups based on potential height and longevity. Additionally, the four most common tree species in the study area were modeled to explore factors affecting tree growth. The average annual mortality rate in the city was 9.97%. Trees located in Institutional land use/land cover (LULC) had the highest annual mortality rate (19.2%/yr), and commercial had the lowest (3.1%/yr). Overall, growth rates for the study area (0.70 cm/yr) and residential LULC (0.80 cm/yr) were comparable to other studies. Growth rates for trees in forested areas were higher (0.56 cm/yr) than those previously reported. Individual species-level growth rates such as those for Juniperus virginiana (1.24 cm/yr) and Quercus virginiana (1.08 cm/yr) were different than other species values reported in other studies. Maintenance activities, site conditions, soil properties, tree characteristics, and LULC significantly influenced urban tree growth, mortality, and in-growth. Results can be used to better understand urban forest ecosystem structure and services in medium sized, subtropical cities and to make better decisions regarding planting and maintenance strategies.